2017
DOI: 10.1186/s13058-017-0838-1
|View full text |Cite
|
Sign up to set email alerts
|

TIMELESS contributes to the progression of breast cancer through activation of MYC

Abstract: BackgroundBreast cancer is the most common malignancy and the leading cause of cancer death among women. TIMELESS (TIM), a circadian rhythm regulator, has been recently implicated in the progression of human cancer. However, the role of TIM in the progression of breast cancer has not been well-characterized.MethodsImmunohistochemistry (IHC) staining was used to examine TIM levels in breast cancer specimens. Mammosphere formation analysis and side population analysis were used to examine the effect of TIM on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 36 publications
3
40
0
Order By: Relevance
“…A recent study confirmed that TIMELESS levels in both breast cancer cell lines and tissues were significantly over-expressed. Upregulation of TIMELESS dramatically enhanced, while knockdown of TIMELESS suppressed the self-renewal of cancer stem cells (CSCs), cell invasion and migration abilities of breast cancer cells in vitro [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study confirmed that TIMELESS levels in both breast cancer cell lines and tissues were significantly over-expressed. Upregulation of TIMELESS dramatically enhanced, while knockdown of TIMELESS suppressed the self-renewal of cancer stem cells (CSCs), cell invasion and migration abilities of breast cancer cells in vitro [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tim functions in cell cycle progression, DNA replication, DNA damage response, and telomere length and integrity maintenance 29 , making it a multifaceted factor implicated in aging and death. Tim has drawn more and more attention in recent studies for its role in cancer 30 32 , also indicates its versatility. It also raises the possibility that immune response towards infection is one of the underlying reasons, given that the role of tim as a regulator of immune response has been recently revealed in Planarian 33 .…”
Section: Discussionmentioning
confidence: 99%
“… 14 19 TIMELESS contributes to the progression of breast cancer through activation of MYC. 20 TIMELESS forms a complex with PARP1 and plays a role in the DNA damage response. 21 One study has reported that overexpression of TIMELESS in NPC cell lines results in resistance to cisplatin-induced apoptosis in vitro and in vivo via the Wnt/β-catenin pathway and downstream gene transcription.…”
Section: Discussionmentioning
confidence: 99%